Cardiovascular magnetic resonance imaging - Karamitsos, T; Neubauer, S (Elsevier, 2014)
MRI (magnetic resonance imaging) uses the magnetic properties of the hydrogen nucleus, radio waves and powerful magnets to provide high-quality still and cine images of the cardiovascular system, with and without the use of exogenous contrast (gadolinium). Cardiovascular MRI (CMR) is the gold standard method for the three-dimensional analysis of cardiothoracic anatomy, the assessment of global and regional myocardial function, and viability imaging (late gadolinium enhancement technique). Using first-pass perfusion imaging under vasodilator stress, CMR has high diagnostic accuracy for the identification of myocardial ischaemia. Oedema imaging using T2-weighted techniques is useful for the identification of acute coronary syndromes and myocardial inflammation. Coronary MR imaging is feasible, and indicated particularly for visualizing anomalous coronaries. Its spatial and temporal resolution is inferior to computed tomography or conventional angiography, and the identification and grading of stenoses remain challenging. Molecular imaging may in future allow visualization of unstable plaque. Novel techniques such as T1- and T2-mapping have recently been developed and offer a quantitative measure of tissue characteristics. CMR also provides important prognostic data for many cardiovascular diseases. CMR is now an essential component of an advanced cardiovascular imaging service, and it is anticipated that its role will continue to grow. ©; 2014 Published by Elsevier Ltd.